Nucleotide pyrophosphatase/phosphodiesterases (NPPs) including NPP1 and NPP2/ ATX as important drug targets: A patent review (2015-2020). (3rd July 2022) - Bano, Sehrish; Al-Rashida, Mariya; Alharthy, Rima D; Khan, Imtiaz Ali; Iqbal, Jamshed
ABSTRACT: Introduction: Ectobucleotidases are a broad class of extracellular nucleotide and nucleoside hydrolyzing enzymes. Since they play a crucial role in mediating purinergic cell signalling, they are promising therapeutic targets for treatment of a range of disorders, including fibrosis, tumor metastasis, inflammation, multiple sclerosis, and autoimmune diseases. Hence selective inhibtors of ectonulceotidases are of great interest for therapeutic intervention. Area covered: Many compounds have demonstrated promising inhibitory potential against ecto-nucleotide pyrophosphatase/phosphodiesterases (NPPs). The chemistry and clinical applications of NPP inhibitors patented between 2015 and 2020 are discussed in this review. Expert opinion: In recent years, there has been a lot of effort towards finding effective and selective inhibitors of NPPs. Even though a number of inhibitors are known, only a few in vivo investigations have been published. In addition to IOA-289, which has passed Phase Ia clinical trials, potent NPP2/ATX inhibitor compounds such as BLD-0409, IPF and BBT-877 have been placed in phase I clinical studies. Some of the most promising NPP2/ATX inhibitors in recent years are closely related analogs of previously known inhibitors, such as PF-8380. Knowledge of the structure activity relationship of such promising inhibitors can potentially translate into the discovery of more potent and effective inhibitors of NPP.